Antianginal medication after non-invasive diagnosis of coronary artery disease - Tolvanen, Juho (My University, 2026)
Background: Coronary computed tomography angiography (CCTA) enables non-invasive anatomical assessment of coronary artery disease (CAD), while positron emission tomography (PET) myocardial perfusion imaging detects myocardial ischemia. We studied how CCTA and PET findings influence the subsequent use of antianginal medication. Methods: In this observational cohort study, 2260 consecutive patients (40% male, median age 63 years) with new-onset symptoms suggestive of CAD underwent CCTA with selective PET perfusion imaging between 2007 and 2017. Use of beta blockers (BB), nitrates and calcium channel blockers (CCB) was assessed from national registry data on drug purchases from 1 year before to 1 year after imaging. Early myocardial revascularization was recorded within 6 months after imaging. Long-term outcomes included allcause mortality, myocardial infarction (MI) and unstable angina pectoris (UAP). Results: Increasing severity of CAD on CCTA/PET imaging was associated with stepwise increase in antianginal medication use, particularly BBs (35% in patients without CAD vs. 77% in ischemic obstructive CAD, p<0.001) and nitrates (3% vs. 60%, p<0.001). In multivariable analyses, CCTA/PET findings were independently associated with subsequent use of BBs and nitrates, but not CCBs. Only 37% of patients with ischemic obstructive CAD underwent early revascularization. Use of BBs was not associated with the composite outcome of death, MI or UAP in patients with ischemic obstructive CAD (adjusted HR 1.08, 95% CI 0.62-1.89, p=0.777) during long-term follow-up (median 6.4 years). Conclusions: In symptomatic patients evaluated for suspected CAD, hybrid CCTA with selective PET perfusion imaging guides subsequent use of antianginal medication, particularly BBs and nitrates. Only a minority of patients with ischemic CAD undergo revascularization, while most are managed conservatively with medical therapy.
Keywords: adverse cardiac events, antianginal medication, chronic coronary syndromes, computed tomography angiography, hybrid imaging, medical therapy, myocardial ischemia, myocardial perfusion imaging, myocardial revascularization, positron emission tomography